The performance framework: a systems approach to understanding performance management - Saltmarshe, Douglass; McGregor, J. Allister; Ireland, Mark (2003)
The article presents a framework for better understanding the nature of performance in organisations involved in the provision of overseas development assistance (ODA). It uses a case study to illustrate the three main features of the framework which are: goals, performance assessment and performance management. It is asserted that a vibrant performance culture is one which links these features together to form an organisation capable of continual improvement through producing effective learning. Organisational culture determines the nature of linkages between the three sub-systems. The article stresses how the notion of performance may extend beyond various forms of evaluation and scrutiny to being part of a sentient learning system rooted in an organisation's culture and structure. The article concludes with consideration of key issues associated with the generation of reflexive learning organisation operating in the ODA sector. These are concerned with understanding the role and nature of systems, organisational vision, the embracing of diversity, training and accountability. - Reproduced.
Keywords: Performance appraisal